2019
DOI: 10.3310/eme06120
|View full text |Cite
|
Sign up to set email alerts
|

Platelet-rich plasma injection for adults with acute Achilles tendon rupture: the PATH-2 RCT

Abstract: Background Achilles tendon rupture (ATR) has a long healing period, which is challenging for patients and clinicians. Platelet-rich plasma (PRP) is an autologous concentration of platelets thought to improve tendon function recovery. Although preliminary research has indicated positive effects, there is, as yet, no evidence of clinical efficacy from adequately powered robust clinical trials. Objectives The objectives were to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 92 publications
1
9
0
Order By: Relevance
“…Trauma mechanisms that lead to an ATR are now well understood, classically occurring due to a single high-load impact or an acceleration–deceleration mechanism [ 1 , 29 ]. Degenerative changes are present in spontaneous tendon ruptures and may lead to a predisposition to ATR [ 29 , 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Trauma mechanisms that lead to an ATR are now well understood, classically occurring due to a single high-load impact or an acceleration–deceleration mechanism [ 1 , 29 ]. Degenerative changes are present in spontaneous tendon ruptures and may lead to a predisposition to ATR [ 29 , 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Degenerative changes are the most common histological findings in spontaneous tendon ruptures (such as high vascularity, collagen disorganization and hypercellularity relatively close to the ruptured site) and may lead to reduced tensile strength and a predisposition to rupture [ 29 , 37 , 38 ].…”
Section: Mechanisms Of Injurymentioning
confidence: 99%
“…116 were allocated to, and received, placebo. For full details of the trial primary and secondary outcomes refer to the main study paper and monograph [27,28]. Table 1 summarises all of the cell count and growth factor measurements within the L-PRP preparations in the PATH-2 trial.…”
Section: Path-2 Trialmentioning
confidence: 99%
“…For example, one EME project showed that platelet-rich plasma, commonly used in the treatment of Achilles tendon rupture, offers no patient benefits compared with placebo. 47 With continuing growth in the market, 48 and a rapid increase of platelet-rich plasma application in sport injuries in Europe, 49 the finding will help inform clinical decision-makers and limit the cost burden of this treatment in managing Achilles tendon rupture. Box 7 provides another example of avoided cost to the health service.…”
Section: Cost Savingsmentioning
confidence: 99%